Emotion and Identity: Evolutionary Theories: Exploring the Role of Emotions in Identity Theory (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Identity control theory was formed in the context of structuralsymbolic interaction, which attends to the different positions in the socialstructure in which persons with given identities are embedded and to the impactof structural position on identity processes. One of the differences amongsocial positions is the amount of resources the position controls and hence theamount of status accorded to the occupant. I examine the effects of socialstatus on the emotional impacts of the lack of identity verification. Status,conceptualized as a symbolic marker indicating who has control of resources, ishypothesized to have two effects. Status and resources help persons verifytheir identities, and at the same time, help to suffer the consequences of alack of verification. Data from the spousal identity of 286 newly marriedcouples are examined and generally support these hypotheses. The implication ofthese findings for existing theory and future research are discussed . Identity theory grows out of structural symbolic interaction (Stryker[1980] 2002). Two features that are particularly important in structuralsymbolic interaction are society and self. Society is viewed as a stable andorderly structure as reflected in the patterned behavior within and betweensocial actors. When we look at the patterned behavior across social actors andsee how these patterns fit with the patterns of other social actors, we findlarger inter individual patterns that constitute the core of social structure.While actors are creating social structure, they are also receiving feedbackfrom the social structure that influences their behavior. In this way, actorsare always embedded in the very social structure that they are simultaneouslycreating. In this study I develop theoretically the role of emotions inidentity theory by examining individuals' emotional reactions to identity nonverification (in a positive and a negative direction) and identityverification, which occurs once versus repeatedly, and which is perpetrated bya familiar other compared with an unfamiliar other. Predictions from identitycontrol theory (ICT) are used to guide the analysis. An experiment simulates awork situation and invokes the worker role identity. Workers either receivefeedback that is expected, given their worker identity standard(identity verification); feedback that is more positive than they would expect(a lack of identity verification in a positive direction); or feedback that ismore negative than they would expect (a lack of identity verification in anegative direction). The workers' emotional reactions' to each situation areinvestigated. Contrary to ICT, identity non verification in a positivedirection results in positive (not negative) emotions; the persistence ofverifying and non-verifying feedback decreases (rather than increases) theaffective response to the feedback; and feedback from a familiar other does notsignificantly influence actors' emotional reactions. The findings raise somequestions about current thinking in ICT and suggest important extensions foremotions in identity theory.